Analisis Algoritma Roughset Pada Penerimaan Beasiswa - Masrizal Masrizal; Angga Putra Juledi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The BAZNAS Scholarship Institution or LBB is a program and utilization tasked with providing education funds to ensure the continuity of educational programs for underprivileged or poor students as intergenerational accountability. This study aims to find out (1) how is the procedure for distributing zakat funds in the form of scholarships, (2) the obstacles faced in distributing zakat funds in the form of scholarships, (3) the efforts made in overcoming obstacles in distributing zakat funds in the form of scholarships. Collecting data in this study using the method of documentation and interviews. The results of this study indicate that (1) the procedures carried out in providing scholarships are very good, (2) the obstacles experienced in distributing zakat funds in the form of scholarships, namely BAZNAS RantauPrapat City, lack of coordination between BAZNAS and the school, and the amount of scholarship funding have not met educational needs, (3) efforts to overcome these obstacles can be done by good coordination with schools, increasing coordination between BAZNAS and schools, and providing services and facilities for zakat givers.This study aims to analyze the Labuhanbatu Baznas Program in providing scholarships in Labuhanbatu using the Rough Set algorithm. The analysis was carried out based on facts and data obtained at the BAZNAS Rantauprapat office using Rosetta Software for testing. The results of this study produce a rule that can be used to make future decision-making policies during data processing.